Pengaruh Teknologi Digital terhadap Perkembangan Kognitif pada Anak Usia Dini - Deswina Putri Setiawan; Jafrantri Indra Utomo; Ati Kusmawati (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This research aims to analyze the influence and impact of the use of digital technology on cognitive development in underage children. This research also explains how important the role of parents is in supervising and accompanying children's growth and development. With research conducted regarding the influence and impact of the use of digital technology on cognitive development in children, it highlights the role of parents which greatly influences the impact on children, and the result is that children master technology better than their parents, the information obtained by the child is faster, but the habit of excessive use of technology actually has a negative impact on children's social skills and emotional control. the importance of well-structured use of technology and parental supervision of children's cognitive development.